2020
DOI: 10.1161/hypertensionaha.119.14107
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Influence of Nonadherence With Prophylactic Aspirin in Preventing Preeclampsia in High-Risk Pregnancies

Abstract: Aspirin nonadherence and its associated increase in cardiovascular and cerebrovascular events is well described; however, the prevalence of aspirin nonadherence among high-risk pregnant women at risk of preeclampsia and its influence on clinical outcomes remains unclear. Our study examined the prevalence of aspirin nonadherence and resistance among high-risk pregnant women quantitatively (platelet function analyzer 100 and plasma salicylic acid) and clinical outcomes relative to adherence. High-risk pregnant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Interviews were ceased at point of qualitative data saturation which was achieved after the sixth interview. Three of these 6 women in the qualitative study were noted to have >90% adherence in the longitudinal study [20] with <90% adherence in the remaining three women. Characteristics of the women invited to participate in the quantitative study and those in the qualitative study are described in Tables 1 and 2 respectively.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Interviews were ceased at point of qualitative data saturation which was achieved after the sixth interview. Three of these 6 women in the qualitative study were noted to have >90% adherence in the longitudinal study [20] with <90% adherence in the remaining three women. Characteristics of the women invited to participate in the quantitative study and those in the qualitative study are described in Tables 1 and 2 respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Our study identified two key themes, from a patient's perspective, that influenced adherence with prophylactic aspirin in pregnancy: 1) Pill burden and non-intentional omission and 2) Communication and positive relationship with HCPs (Table 3). We previously demonstrated that, from the women's demographic characteristic perspective, women who had previous preeclampsia and tertiary level education had a higher rate of adherence with aspirin [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations